Pengaruh Earning Pershare (EPS), Opini Audit, Return On Equity (ROE), Dan Debt To Equity Ratio (DER) Terhadap Return Saham Pada Perusahaan Yang terdaftar dalam Bursa Efek Indonesia (BEI). - Fedry Gunawan; Yensy Sugianto (Fakultas Ekonomi Prodi Akuntansi, 2021)
The objective of the research was to examine and analyze the influence of Earning per Share, Audit Opinion, Return on Equity and Debt to Equity Ratio on stock return in the property and real estate sector companies listed in the Indonesia Stock Exchange period 2017-2019. The research used descriptive research methode. The population was 48 companies in the property and real estate sector listed in the Indonesia Stock Exchange for the period 2017 – 2019, and 24 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using multiple linear regression using SPSS. The results of the research showed that the variables of Earning per Share, Audit Opinion, Return on Equity and Debt to Equity Ratio simultaneously had influence on Stock Return. Partially, Earning per Share and Debt to Equity Ratio had significant influence on Stock Return. For Audit Opinion and Return on Equity had no significant influence on Stock Return.